Biosynthesis of cobalt oxide nanoparticles using endophytic fungus Aspergillus nidulans. (15th July 2018) - Vijayanandan, Ajuy Sundar; Balakrishnan, Raj Mohan
Abstract: Metallic oxide nanoparticles have profound applications in electrochemical devices, supercapacitors, biosensors and batteries. Though four fungi were isolated from Nothapodytes foetida, Aspergillus nidulans was found to be suitable for synthesis of cobalt oxide nanoparticles, as it has proficient tolerance towards metal under study. The broth containing precursor solution and organism Aspergillus nidulans had changed from pink to orange indicating the formation of nanoparticles. Characterization by x-ray diffraction analysis (XRD), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR) and energy dispersive x-ray analysis (EDX) confirmed the formation of spinel cobalt oxide nanoparticles at an average size of 20.29 nm in spherical shape with sulfur-bearing proteins acting as a capping agent for the synthesized nanoparticles. The nanoparticles could be applied in energy storage, as a specific capacitance of 389 F/g showed competence. The study was a greener attempt to synthesize cobalt oxide nanoparticles using endophytic fungus. Graphical abstract: Image 1 Highlights: First attempt to synthesize cobalt oxide nanoparticles through endophytic fungus. The average size of synthesized nanoparticles is 20.29 nm. Protein capping act as stabilizing agent for nanoparticles. Extracellular synthesis makes the process simple.